Keberlakuan Hukum Penodaan Agama di Indonesia Antara Tertib Hukum dan Tantangan Hak Asasi Manusia - Heru Susetyo; Farida Prihatini; Abdurakhman; Nurindah Hilimi; Intan Mahabah; Ira Apriyanti; Suri Rahmadhani (Perspektif Hukum, 2020)
Indonesia with its five pillars of Pancasila binds the State and its citizens to "Believe in Almighty" where the religious identity is the spirit of the State that must be respected. This is proven by the existence of Law No. 1/PNPS/1965 concerning the Prevention of Blasphemy that prohibits blasphemy, atheism, or any belief other than the religious identity recognized by the government and law. Article 156 (a) of the criminal code, known as the Criminal Code, also punishes "the dissemination of information aimed at inciting religious hatred or hostility" for five years in prison. In addition, the Information and Electronic Transaction Law (ITE) Law No. 11 of 2008, regulating criminal sanctions for libel, hate speech, and insulting certain religions/beliefs through electronic devices. On the other hand, the 1945 Constitution, as well as the Human Rights Act of 1999 and Law No. 12/2005 concerning Ratification of the ICCPR guarantees freedom of expression, religion, and belief. Criticism of religion is quite limited and support for atheism is definitely still banned in Indonesia. Therefore, this article yearns to explore the dynamics of law enforcement and defamation in Indonesia in national and international human rights regimes. Then, does the law on blasphemy have a legal basis in the Indonesian legal system, national and international human rights regimes, and the surrounding social values? This study compares the application of religious blasphemy laws in several regions in Indonesia and in several Southeast Asian countries.